2014
DOI: 10.1097/mao.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence in Association With Quality of Life in Patients Recently Diagnosed With Vestibular Schwannoma

Abstract: The substantial impact of a vestibular schwannoma-diagnosis on a psychological measure (i.e., Emotional Intelligence) in the affected patients as demonstrated in our study has important clinical and research implications when developing guidelines about counselling of these patients. This also has to be taken into account when making clinical decisions about the proposed treatment. Addressing Emotional Intelligence may be helpful in the development of a self-management program for patients with vestibular schw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…A possible explanation for this finding is that hearing and balance disorders have a major impact on daily life. This has already been established in previous research . Another remarkable finding was the correlation between the reflection of negative emotions in the drawings and QoL.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A possible explanation for this finding is that hearing and balance disorders have a major impact on daily life. This has already been established in previous research . Another remarkable finding was the correlation between the reflection of negative emotions in the drawings and QoL.…”
Section: Discussionsupporting
confidence: 81%
“…In the context of the CSM, sociodemographic, clinical, and psychological factors (i.e., illness perceptions) are the main determinants, not only in patients with VS, but in any illness category. Identified determinants of QoL in patients with VS before, during, and after treatment are male gender, balance disorders, vertigo, hearing loss, facial nerve or trigeminal nerve dysfunction, microsurgical resection, psychological factors (i.e., optimism, control), emotional intelligence, and IPs …”
Section: Introductionmentioning
confidence: 99%
“…The patient in the present case is the youngest from the reported cases, and the average age of the OECT patients is 34.1 years (range, 20-49 years). This is younger than that of patients with schwannomas (9). As OECTs are located in the anterior fossa close to the olfactory nerve, olfactory dysfunction is a common clinical manifestation (1,(3)(4)(5)(6)(7)(8).…”
Section: Intraoperative Findingsmentioning
confidence: 99%
“…[15] In other studies, the relationship between EI and some dimensions of HRQoL was investigated in older adults,[23] as well as patients with vestibular schwannoma. [28] Interventional studies incorporating EI training programs have also involved different patient populations including those with type-II diabetes mellitus,[29] and asthma. [30] The results demonstrated that EI training programs led to an increase in total QoL scores of the interventional diabetic group.…”
Section: Introductionmentioning
confidence: 99%